ANALISIS PUBLIKASI PUTUSAN HUKUM YANG MEMUAT IDENTITAS ANAK YANG BERHADAPAN DENGAN HUKUM: Analysis of the Publication of Judges’ Decisions Containing the Identity of Children in Conflict with the Law - Danasari, Putu Angel Putri; Setiyono (Faculty of Law, Universitas Trisakti, 2024)
Abstract In accordance with the applicable guidelines, children who have problems with the law cannot publish their identities in court decisions that are disseminated on paper or electronic media. However, there is a judge’s decision that publishes the child’s identity. This article raises the issue of whether the publication of judge’s decisions containing the identity of a child violates Law Number. 11 of 2012 and the Decree of the Chief Justice of the Supreme Court Number: 1-144/KMA/SK/I/2011 and what are the legal consequences for the publication of a judge’s decision containing the identity of a child in conflict with the law. The research was conducted normatively based on secondary data and primary data. Data analysis was carried out descriptively and conclusions were drawn using deductive methods. Based on the analysis, it can be concluded that the judge’s decision to publish the identity of a child in conflict with the law has violated Article 3 letter I in conjuction with Article 19 Paragraph (1) of law Number 11 of 2012 and the Decree of the Chief Justice of the Supreme Court of the Republic of Indonesia Number: 1-144/KMA/SK/I/2011. Children who suffer losses as result of their identity being published can file a civil lawsuit to obtain compensation.